(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines the training of football players, conducts research on the organization of complex training of football players at the stages of long-term training, as well as testing of players who regularly engage in long-term training. studied in detail. The aspects that should be paid attention to when testing various qualities of players aged 11-13 are studied. The results of control tests were statistically analyzed and conclusions were made.